Total phenolic and flavonoid contents and their antioxidant capacity of Curcuma xanthorrhiza accessions from Jambi (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Asyhar R, Minarni M, Arista RA, Nurcholis W. 2023. Total phenolic and flavonoid contents and their antioxidant capacity of Curcuma xanthorrhiza accessions from Jambi. Biodiversitas 24: 5007-5014. Curcuma xanthorrhiza Roxb., is an effective natural antioxidant and is widely used as a raw material for jamu in Indonesian traditional medicine. This study aims to evaluate the biochemical characteristics and antioxidant capacity of C. xanthorrhiza rhizome accessions. Ten accessions of C. xanthorrhiza rhizome from 10 districts in Jambi province were evaluated for total phenolic (TPC) and total flavonoid (TFC) content and antioxidant capacity using four methods: 2,2-diphenyl picrylhydrazyl (DPPH), 2,2 azinobis (3-ethyl benzothiazoline) -6-sulfonic acid (ABTS), ferric reducing antioxidant power (FRAP), and cupric reducing antioxidant power (CUPRAC). The content of total phenolic (TPC) and total flavonoids (TFC) varied from 1.74±0.085 to 18.72±1.47 mg GAE/g DW and 1.74±0.085 to 18.72±1.47 mg GAE/g DW, respectively. Antioxidant capacities ranged from 0.13-1.11, 0.72-4.14, 7.71-81.48, 18.37-211.68 µmol TE/g DW, assayed by DPPH, ABTS, FRAP, and CUPRAC methods, respectively. Antioxidant activity was significantly correlated with the polyphenol content of C. xanthorrhiza rhizome accessions. Accession to C. xanthorrhiza rhizome with the code JSS, JBE, JG, and JK has the capacity for polyphenolic compounds (phenolics and flavonoids) and antioxidant capacity compared to other accessions, indicating that these accessions are promising for further breeding programs and commercial purposes.